Modern Technologies For Sustainable Agriculture - Kumar, Sunil (New India Publishing Agency (NIPA), 2021)
Application of biotechnology in Hi-tech agriculture/Atul Kumar and Vandana A. Kumar. 2. Crop selection an efficient tool for sustainable agricultural production in the impending climate change situation/Anil Kumar Singh, U.R. Sangle and Pravesh Kumar. 3. Management of soil fertility for sustainable vegetable production/Sobaran Singh, S.K. Maurya and Poonam Gangola. 4. Microbial inoculation through endophytic bacteria for sustainable agriculture/K. Swarnalakshmi, M. Senthikumar and Sanjay Sachan. 5. Seed enhancement technologies for assured plant stand establishment/S.K. Yadav, Arun Kumar M.B., Sangita Yadav, S.R. Jacob, V.A. Tonapi and Priya Ranjan Kumar